Stereotactic Radiosurgery for Cushing Disease: Results of an International, Multicenter Study - Mehta, Gautam U; Ding, Dale; Patibandla, Mohana Rao; Kano, Hideyuki; Sisterson, Nathaniel; Su, Yan-Hua; Krsek, Michal; Nabeel, Ahmed M; El-Shehaby, Amr; Kareem, Khaled A; Martinez-Moreno, Nuria; Mathieu, David; et al. (The Journal of clinical endocrinology and metabolism, 2017)
Context: Cushing disease (CD) due to adrenocorticotropic hormone-secreting pituitary tumors can be a management challenge. Objective: To better understand the outcomes of stereotactic radiosurgery (SRS) for CD and define its role in management. Design: International, multicenter, retrospective cohort analysis. Setting: Ten medical centers participating in the International Gamma Knife Research Foundation. Patients: Patients with CD with >6 months endocrine follow-up. Intervention: SRS using Gamma Knife radiosurgery. Main Outcome Measures: The primary outcome was control of hypercortisolism (defined as normalization of free urinary cortisol). Radiologic response and adverse radiation effects (AREs) were recorded. Results: In total, 278 patients met inclusion criteria, with a mean follow-up of 5.6 years (0.5 to 20.5 years). Twenty-two patients received SRS as a primary treatment of CD. Mean margin dose was 23.7 Gy. Cumulative initial control of hypercortisolism was 80% at 10 years. Mean time to cortisol normalization was 14.5 months. Recurrences occurred in 18% with initial cortisol normalization. Overall, the rate of durable control of hypercortisolism was 64% at 10 years and 68% among patients who received SRS as a primary treatment. AREs included hypopituitarism (25%) and cranial neuropathy (3%). Visual deficits were related to treatment of tumor within the suprasellar cistern (P = 0.01), whereas both visual (P < 0.0001) and nonvisual cranial neuropathy (P = 0.02) were related to prior pituitary irradiation. Conclusions: SRS for CD is well tolerated and frequently results in control of hypercortisolism. However, recurrences can occur. SRS should be considered for patients with persistent hypercortisolism after pituitary surgery and as a primary treatment in those unfit for surgery. Long-term endocrine follow-up is essential after SRS.
Keywords: adenom hypofýzy vylučující ACTH; dospělí; Adenoma; Female; dítě; hypersekrece ACTH v hypofýze; Adult; výsledek terapie; mladý dospělý; ženské pohlaví; adenom; Adolescent; lidé; ACTH-Secreting Pituitary Adenoma; Treatment Outcome; Aged, 80 and over; následné studie; radiochirurgie; retrospektivní studie; Radiosurgery; Follow-Up Studies; Male; Pituitary ACTH Hypersecretion; Aged; Young Adult; lidé středního věku; Child; senioři nad 80 let; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; mladiství; Humans